Capillary Haemangioma of Gingiva - A Rare Lesion - Manohar, B; Meena, V; Metgud, R; Bhavaneshwari, S; Humagain, M (Kathmandu University Medical Journal, 2023)
Capillary Haemangioma is a benign vascular tumour characterized by proliferation of blood vessels with a very striking similarity to pyogenic granuloma with a predilection to occur on the gingiva. Though the head and neck are the most common region of occurrence, but is considered to be rare occurring on the gingiva, intra-orally. The lesion clinically mimicked pyogenic granuloma but was histopathologically diagnosed as capillary haemangioma. It was surgically excised and followed up for 6 months without any recurrence.